Using the oocyte donation model to identify early trophoblast pregnenolone production - Licciardi, Frederick (Springer US, 2013)
PURPOSE: To investigate production of progesterone’s precursor, pregnenolone, in the early oocyte donation pregnancy. METHODS: Pregnenolone and progesterone were measured on luteal days 21, 28, 35, 60 and 80. Progesterone was measured via the Immulite system, pregnenolone by liquid chromatography separation with tandem mass spectrometric detection. RESULTS: Progesterone rose significantly from days 35 today 60. Pregnenolone likewise rose significantly from days 35–60, but at a much higher rate, with an increase of 57 % by day 60, 75 % to day 80. The increase in pregnenolone was statistically more significant than the increase in progesterone (p < .05). CONCLUSIONS: This is the first report describing that progesterone’s precursor, pregnenolone, increases with time in the very early pregnancy. Because no corpus luteum is present in oocyte recipients, the main source of pregnenolone is the early placenta. Measurements of pregnenolone may provide information concerning early trophoblast function and may represent a method of assessing placental competency.